Stalacris Desutter-Grandcolas n. gen., an amazing cricket from South Africa (Orthoptera, Grylloidea, Phalangopsidae) - Desutter-Grandcolas, Laure (Zootaxa, 2013)
Stalacris n. gen. (Insecta, Grylloidea, Phalangopsidae) is described from South Africa using characters of morphology and male genitalia. This taxon, known from only two species, Stalacris meridionalis n. gen., n. sp. and Stalacris sp, is characterized by the unique structure of its forewings. These are prolonged distally as long, acute and more or less artic-ulated processes, forming a kind of forceps when forewings are opened.